Highly heat-resistant coating composition
The high heat-resistant coating composition, featuring a polysilazane compound and an inorganic filler, addresses the challenges of maintaining film thickness and preventing cracking at high temperatures, achieving effective heat resistance and thick film formation.
Patent Information
- Application Number
- JP2022005742
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-18
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2042-01-18
AI Technical Summary
Existing coating materials struggle to provide high heat resistance and thick film formation while maintaining film thickness and preventing cracking or peeling, especially at temperatures around 400°C.
A high heat-resistant coating composition comprising a polysilazane compound with specific structural components and an inorganic filler with a melting point and decomposition temperature of 400°C or higher, which together provide durability and thick film capabilities.
The coating composition achieves minimal film loss at high temperatures, allows for thick film formation to cover substrate unevenness, and exhibits excellent heat resistance and crack resistance.
Smart Images

Figure 0007657744000001 
Figure 0007657744000002 
Figure 0007657744000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a high heat resistant coating composition. [Background technology]
[0002] In recent years, with the increasing sophistication of electronic devices, the performance of electronic components used has become increasingly high. In particular, surface coatings have been increasingly used to physically and chemically protect component materials in order to improve reliability. In the past, materials that had both functionality and stability over time were used, but the level of functionality required for electronic devices has become significantly higher in recent years due to the increasing sophistication of electronic devices. Therefore, component materials have been specialized for high performance, and stability over time has been given by surface coatings, etc. However, even when the same characteristics are to be given to electronic components, coatings must be made using different methods and materials depending on the environment, shape, and manufacturing method in which the components are used, and coating materials and methods that correspond to various required characteristics must be prepared. However, the current situation is that methods and coating materials that meet the requirements of each component have not been sufficiently proposed.
[0003] One coating that remains problematic is thick-film coating, which requires high heat resistance. In particular, there is a demand for a hole-filling coating that covers and flattens the unevenness of a substrate, and a coating material that does not deteriorate even at high temperatures of about 400°C. Silicone-based coating materials, which are generally said to have higher heat resistance than organic coating materials, have a heat resistance of about 250°C, so silicone resin coatings have traditionally been used as heat-resistant coatings (for example, Patent Document 1). However, in recent electronic components, high heat resistance of 300 to 400°C is sometimes required, and conventional silicone resin-based coating materials cannot meet this requirement.
[0004] To solve this problem, a method has been proposed in which silicone resin, which is more heat-resistant than organic resins, is baked at high temperatures to perform a treatment similar to that used for baking paint for acrylic resins and melamine resins (Patent Document 2). It has been reported that this method improves the heat resistance of the coating film at 400°C, but the film thickness is significantly reduced during baking due to the curing shrinkage of the coating film and the volatilization of the coating film components, making it difficult to use the film as a hole-filling coating to fill in the unevenness of the substrate. For hole-filling applications, it is necessary to maintain the film thickness at the time of application even during curing and high-temperature heating.
[0005] On the other hand, inorganic coating materials such as sol-gel glass have high heat resistance of nearly 1,000°C, and can be formed into films by wet processes or dry processes such as CVD, so that different manufacturing methods can be used depending on the substrate (Patent Document 3). However, inorganic coating agents shrink significantly when cured, and if the film thickness is increased, cracks and peeling occur during curing due to shrinkage stress, so they can basically only be used with a film thickness of 1 μm or less. In the case of chemical protection of surfaces, a thin film coating of 1 μm or less can be expected to be sufficiently effective, but it cannot be used for applications such as filling and flattening unevenness on the surface of parts such as semiconductor trenches. In order to solve this problem, many methods have been reported in which inorganic fillers are added to inorganic coating materials, similar to the above-mentioned method of increasing the heat resistance of silicone resins, but the film thickness is thin, at only a few μm, and it cannot be used to cover unevenness.
[0006] In addition, a method using polysilazane as another inorganic coating material has been proposed (Patent Document 4). Like sol-gel glass, polysilazane can form a glass film by wet coating, and has a high film density and excellent heat resistance compared to sol-gel glass. In addition, sol-gel glass cannot be exposed to high temperatures because components such as water and alcohol tend to remain in the film, which expand at high temperatures and cause the film to burst. On the other hand, polysilazane has a small molecular size of the detached components and is unlikely to remain in the film, so there is no concern about film bursting even at high temperatures. However, inorganic polysilazanes that form silica glass after curing are difficult to form thick films like sol-gel glass, and organic group-modified polysilazanes that contain a large amount of organic groups have little cure shrinkage and can form thick films, but have the problem of low bond strength after curing and poor durability at high temperatures.
[0007] In view of these problems, there is a demand for a coating composition that is durable at high temperatures of about 400° C. and can form a thick film capable of covering the irregularities of a substrate. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2005-206761 A [Patent Document 2] Japanese Patent Application Publication No. 6-001847 [Patent Document 3] Japanese Patent Application Publication No. 11-043782 [Patent Document 4] JP 2014-191841 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a coating composition which is less prone to film loss at high temperatures and has high heat resistance that allows for the formation of thick films. [Means for solving the problem]
[0010] In order to achieve the above object, the present invention provides The present invention provides a highly heat-resistant coating composition comprising the following component (A) and component (B): (A) A polysilazane compound containing a structure represented by the following general formula (A-1) and / or a structure represented by the following general formula (A-2), wherein the total amount of the structure represented by the general formula (A-1) and the structure represented by the general formula (A-2) is 50 to 100 mass % based on the entire polysilazane compound: (B) Inorganic filler with a melting point and decomposition temperature of 400°C or higher [ka] (In the formula, R 1 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 1 may be the same or different.) [ka] (In the formula, R 2 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 2 may be the same or different.)
[0011] Such a coating composition will have little film loss at high temperatures and will be a highly heat-resistant coating composition that can be made thicker.
[0012] In addition, R in the general formula (A-1) 1 is preferably a methyl group.
[0013] In this case, the polysilazane compound has excellent stability and workability.
[0014] In addition, R in the general formula (A-2) 2 is preferably a methyl group.
[0015] In this case, the highly heat-resistant coating composition of the present invention will have excellent curing speed and film properties after curing.
[0016] The component (B) is preferably selected from the group consisting of silica, alumina, zinc oxide, and titanium oxide.
[0017] Such a material has excellent wettability and dispersibility with the polysilazane compound.
[0018] The average particle size of the component (B) is preferably within the range of 5 to 100 nm.
[0019] Within this range, the dispersibility in the polysilazane compound is good, and the transparency of the coating film is improved.
[0020] The amount of the component (B) is preferably 50 to 500 parts by mass per 100 parts by mass of the component (A).
[0021] Within this range, the crack resistance and heat resistance of the coating composition are sufficiently exhibited, and the coating composition has good workability and is easy to apply. Effect of the Invention
[0022] As described above, the highly heat-resistant coating composition of the present invention is a composition containing a polysilazane compound containing a specific structure in a certain amount or more and an inorganic filler, and it is possible to obtain a coating composition that is less prone to film loss even at high temperatures of about 400°C and has the characteristics of being able to be applied in a thick film (able to make a thick film). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] As described above, there has been a demand for a coating composition that is durable at high temperatures of about 400° C. and capable of forming a thick film capable of covering the irregularities of a substrate.
[0024] As a result of intensive research aimed at solving the above problems, the present inventors have found that by using a polysilazane compound containing a certain amount or more of a specific structure, durability at high temperatures of about 400° C. can be improved and a thick film capable of covering unevenness of a substrate can be formed, thereby completing the present invention.
[0025] That is, the present invention provides: The highly heat-resistant coating composition comprises the following component (A) and component (B): (A) A polysilazane compound containing a structure represented by the following general formula (A-1) and / or a structure represented by the following general formula (A-2), wherein the total amount of the structure represented by the general formula (A-1) and the structure represented by the general formula (A-2) is 50 to 100 mass % based on the entire polysilazane compound: (B) Inorganic filler with a melting point and decomposition temperature of 400°C or higher [ka] (In the formula, R 1 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 1 may be the same or different.) [ka] (In the formula, R 2 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 2 may be the same or different.)
[0026] The present invention will be described in detail below, but the present invention is not limited thereto.
[0027] [(A) Polysilazane compound] The polysilazane compound used in the coating composition of the present invention is characterized in that it contains a specific structure represented by the following general formula (A-1) and / or the following general formula (A-2) in a certain amount or more relative to the entire polysilazane compound.
[0028] (Polysilazane Structure (A-1)) The polysilazane structure (A-1) is a structure represented by the following general formula (A-1). [ka] (In the formula, R 1 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 1 may be the same or different.)
[0029] R in the above general formula (A-1) 1 Examples of the groups include methyl, ethyl, and phenyl groups, and may be the same or different within the molecule. Among these, a methyl group is preferred from the viewpoint of the stability and workability of the resulting polymer. Hereinafter, the portion of component (A) that is made of the polysilazane structure (A-1) will be referred to as component (A-1).
[0030] (Polysilazane Structure (A-2)) The polysilazane structure (A-2) is a structure represented by the following general formula (A-2). [ka] (In the formula, R 2 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 2 may be the same or different.)
[0031] R in the above general formula (A-2) 2 Examples of the groups include methyl, ethyl, and phenyl groups, and may be the same or different within the molecule. Among these, a methyl group is preferred from the viewpoint of the curing speed and the film properties after curing. Hereinafter, the portion of component (A) that is made of the polysilazane structure (A-2) is referred to as component (A-2).
[0032] (Other polysilazane structures) The polysilazane compound of component (A) may also contain, as another polysilazane structure, a portion (component (A-3)) consisting of a structure represented by the following general formula (A-3) (polysilazane structure (A-3)) other than the above components (A-1) and (A-2). [ka] (In the formula, R 3 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 3 may be the same or different. 4 is a group selected from a hydrogen atom, an aliphatic hydrocarbon group having 1 to 6 carbon atoms, and an aromatic hydrocarbon group having 6 to 12 carbon atoms. In the polysilazane compound, R 4 may be the same or different.)
[0033] R in the above general formula (A-3) 3 Examples of R include a methyl group, an ethyl group, a phenyl group, etc., and may be the same or different within the molecule. Among them, a methyl group is preferable from the viewpoint of stability over time and film properties after curing. 4 For example, may be a hydrogen atom, a methyl group, an ethyl group, a propyl group, etc., and may be the same or different within a molecule. Among them, a hydrogen atom is preferable from the viewpoint of curing speed and removal of components eliminated during curing.
[0034] In the present invention, taking into consideration the balance between workability, curing speed, and cured product properties, the total of the (A-1) component and the (A-2) component must be 50 to 100% by mass relative to 100% by mass of the polysilazane compound. This range is preferable because it provides good workability during coating, and good crack resistance and heat resistance of the cured coating film.
[0035] In addition, the component (A-1) or the component (A-2) may be used alone, and the ratio of the components (A-1) and (A-2) is arbitrary.
[0036] If the total amount of the (A-1) and (A-2) components is less than this ratio, the polymer stability will be too high or too low, resulting in an inappropriate curing speed and a clean coating film. In addition, the above structure contributes greatly to the hardness of the cured coating film, so outside the above range, appropriate hardness cannot be obtained.
[0037] Since the total amount of the components (A-1) and (A-2) is 50 to 100% by mass relative to 100% by mass of the polysilazane compound, the amount of the component (A-3) can be 0 to 50% by mass relative to 100% by mass of the polysilazane compound.
[0038] In addition, the (A) component is preferably contained in an amount of 15% by mass or more based on the entire high heat-resistant coating composition of the present invention. The (A-1) and (A-2) components can form a uniform, hard coating film after curing, but at the same time, they also have flexibility against stress. A soft coating film has weak bonds between the coating film components, and the bonds are broken and volatilized at high temperatures, so the coating film is prone to film loss. On the other hand, a hard coating film cannot keep up with the thermal expansion of the substrate and coating film components at high temperatures, and is prone to cracking and peeling. In the present invention, by combining coating film hardness and flexibility, it is possible to obtain both contradictory properties of film loss at high temperatures and prevention of cracking.
[0039] The molecular weight of the polysilazane compound is not particularly specified, but from the viewpoint of workability such as curing speed and viscosity, the weight average molecular weight is preferably within the range of 500 to 500,000. If the weight average molecular weight is 500 or more, curing proceeds quickly and the coating film is not tacky, which is preferable, and if it is 500,000 or less, it has an easy-to-handle viscosity and is unlikely to harden during use, which is preferable. The weight average molecular weight was measured using a GPC (gel permeation chromatography) device by the following method.
[0040] [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.6mL / min Detector: UV detector Column: TSK Guardcolumn SuperH-L TSKgel SuperMultipore HZ-M (4.6mm I.D. x 15cm x 4) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (0.5 wt% THF solution)
[0041] (B) Inorganic filler The inorganic filler used in the present invention is not particularly limited as long as it has a melting point and decomposition temperature of 400° C. or higher. In order to satisfy the heat resistance at temperatures of 250 to 400° C., which silicone resin cannot meet, the inorganic filler used in the present invention must not undergo dissolution or decomposition reactions in this temperature range.
[0042] The melting point and decomposition temperature of the inorganic filler can be measured from the weight change and heat change by thermogravimetric differential thermal analysis (TG-DTA).
[0043] Examples of the inorganic filler that satisfies these conditions include metals such as aluminum, silicon, titanium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, palladium, silver, and tungsten, metal oxides such as aluminum oxide (alumina), silicon oxide (silica, silica glass), titanium oxide, iron oxide, copper oxide, zinc oxide, and zirconium oxide, and metal nitrides such as boron nitride, aluminum nitride, and silicon nitride. Among these, silica, alumina, zinc oxide, and titanium oxide, which have excellent wettability and dispersibility with polysilazane, are preferred, and nanosilica (silica with an average particle size of 100 nm or less), which tends to give a transparent coating film appearance in terms of refractive index, is more preferred.
[0044] The inorganic filler preferably has a small average particle size, specifically, within the range of 5 to 100 nm. Within this range, the inorganic filler has good dispersibility in the polysilazane compound, and the transparency of the coating film is improved.
[0045] The inorganic filler average particle size is a volume-based average particle size, and can be measured by a laser diffraction / scattering type particle size distribution measuring device.
[0046] The amount of the inorganic filler (component (B)) added is preferably within a range of 50 to 500 parts by mass relative to 100 parts by mass of the polysilazane compound (component (A)). If it is 50 parts by mass or more, the crack resistance and heat resistance of the coating composition are sufficiently exhibited, and if it is 500 parts by mass or less, the workability is good and coating is easy.
[0047] [Other additives] If necessary, a curing catalyst, a diluting solvent, etc. may be added to the coating composition of the present invention.
[0048] The curing catalyst is not particularly limited as long as it has the effect of promoting the curing reaction of the polysilazane compound.
[0049] Specific examples of the curing catalyst include organic acids such as carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, linoleic acid, linoleic acid, oleic acid, and oxalic acid, hydroxycarboxylic acids such as malic acid and citric acid, d-block elements belonging to the fourth period of the periodic table such as titanium, manganese, cobalt, nickel, and zinc, platinum group elements such as ruthenium, rhodium, palladium, osmium, iridium, and platinum, and amphoteric elements such as aluminum, tin, and zinc, or compounds containing these elements. Among these, palladium acetate and palladium propionate are preferred because they promote the curing reaction with the addition of a small amount and are soluble in the solvent.
[0050] The mixing ratio with the polysilazane compound is not particularly limited since it varies depending on the composition of the polysilazane compound and the type of the curing catalyst added, but in the case of palladium acetate, it is preferably within the range of 0.01 to 2 parts by mass per 100 parts by mass of the polysilazane compound. Within this range, it has an excellent balance between curing speed and workability when used as a coating material.
[0051] The dilution solvent may be used to improve workability during coating. Examples of the dilution solvent include alkane compounds such as n-hexane, n-octane, and n-nonane, alkene compounds such as 1-octene, 1-nonene, and 1-decene, cycloalkane compounds such as cyclohexane, methylcyclohexane, and dimethylcyclohexane, ester compounds such as n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, isoamyl acetate, and ethyl caproate, and ether compounds such as diethyl ether, dibutyl ether, and ethylene glycol diethyl ether. Naphthene-based solvents such as Exxol DSP145 / 160 can also be used as the dilution solvent.
[0052] The dilution solvent may be used to adjust the viscosity of the composition or to improve the wettability of the composition to the substrate, but it is preferable that the non-volatile content of the polysilazane compound is not less than 50% by mass. If the non-volatile content is 50% by mass or more, the dilution solvent is unlikely to remain in the cured product, and voids and discoloration are unlikely to occur when exposed to high temperatures, which is preferable.
[0053] In preparing the composition of the present invention, a dispersion of the inorganic filler (B) can be used. A solvent such as anisole may also be added to the composition of the present invention.
[0054] The present invention relates to a coating composition that is durable at high temperatures of about 400° C. and can form a thick film capable of covering the irregularities of a substrate.
[0055] Examples of methods for applying the highly heat-resistant coating composition of the present invention include roll coating methods using a chamber doctor coater, a single roll kiss coater, a reverse kiss coater, a bar coater, a reverse roll coater, a forward rotation roll coater, a blade coater, a knife coater, etc., spin coating methods, dispensing methods, dipping methods, spraying methods, transfer methods, slit coating methods, etc.
[0056] The substrate to be coated is not particularly limited, but examples thereof include highly heat-resistant organic synthetic resins such as polyimide resin (PI) and bismaleimide resin (BMI), metals such as aluminum, silicon, iron, nickel, copper, silver, and gold, oxides such as alumina, silica, titanium oxide, and zinc oxide, and nitrides such as boron nitride, aluminum nitride, silicon nitride, and gallium nitride. The substrate surface may have irregularities.
[0057] The thickness of the coating film varies depending on the difference in linear expansion coefficient from the substrate and the temperature to which it is exposed, but is generally 0.1 to 100 μm, preferably 0.5 to 50 μm, in terms of cured film thickness. The composition of the present invention can form a thick film capable of covering the unevenness of the substrate.
[0058] As a coating method, it is preferable to form an uncured coating film of the polysilazane compound by coating the substrate by any method, and then heat and dry the coating film. This step is aimed at completely removing the solvent and low molecular weight components contained in the coating film, but is not necessarily required when the coating film does not contain a solvent.
[0059] The heating and drying temperature is usually in the range of room temperature (25° C.) to 300° C., preferably 70° C. to 150° C. Preferred treatment methods for the heating and drying step include heat treatment, microwave treatment, infrared treatment, etc. Curing proceeds even at room temperature, but curing can be made even faster by heating. EXAMPLES
[0060] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, parts refer to parts by mass. The weight average molecular weight of component (A), the melting point and decomposition temperature of component (B), and the average particle size were measured by the above-mentioned methods.
[0061] [Synthesis example A] 378g of methyltrichlorosilane and 326g of dimethyldichlorosilane were added as halogenated silane raw materials to 4,000g of pyridine, and ammonia gas was blown into the liquid at 1.0L / min for 430 minutes to cause a reaction. At this time, white ammonium chloride salt was generated and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off pyridine, obtaining polysilazane compound A. The weight-average molecular weight of this polysilazane compound was measured and found to be 2,700. In addition, in 100% by mass of this polysilazane, the (A-1) component was 50% by mass, the (A-2) component was 0% by mass, and the (A-3) component was 50% by mass.
[0062] [Synthesis example B] 529g of methyltrichlorosilane and 196g of dimethyldichlorosilane were added to 4,000g of pyridine as halogenated silane raw materials, and ammonia gas was blown into the liquid at 1.0L / min for 460 minutes to cause a reaction. At this time, white ammonium chloride salt was generated and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off pyridine, obtaining polysilazane compound B. The weight-average molecular weight of this polysilazane compound was measured and found to be 3,800. In addition, in 100% by mass of this polysilazane, the (A-1) component was 70% by mass, the (A-2) component was 0% by mass, and the (A-3) component was 30% by mass.
[0063] [Synthesis example C] 582 g of monomethyldichlorosilane was added to 4,000 g of pyridine as a halogenated silane raw material, and ammonia gas was blown into the liquid at 1.0 L / min for 400 minutes to cause a reaction. At this time, white ammonium chloride salt was generated and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off pyridine, obtaining polysilazane compound C. The weight-average molecular weight of this polysilazane compound was measured and found to be 1,200. In addition, in 100 parts by mass of this polysilazane, the components (A-1) and (A-3) were 0% by mass, and the component (A-2) was 100% by mass.
[0064] [Synthesis example D] (for comparison) 227g of methyltrichlorosilane and 456g of dimethyldichlorosilane were added as halogenated silane raw materials to 4,000g of pyridine, and ammonia gas was blown into the liquid at 1.0L / min for 430 minutes to cause a reaction. At this time, white ammonium chloride salt was generated and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off pyridine, obtaining polysilazane compound D. The weight-average molecular weight of this polysilazane compound was measured and found to be 1,700. In addition, in 100% by mass of this polysilazane, the (A-1) component was 30% by mass, the (A-2) component was 0% by mass, and the (A-3) component was 70% by mass.
[0065] [Synthesis example E] (for comparison) 582 g of dimethyldichlorosilane was added to 4,000 g of pyridine as a halogenated silane raw material, and ammonia gas was blown into the liquid at 1.0 L / min for 400 minutes to cause a reaction. At this time, white ammonium chloride salt was generated and removed by filtration. The filtrate was heated at 100°C under a reduced pressure of about 800 Pa to distill off pyridine, obtaining polysilazane compound E. The weight-average molecular weight of this polysilazane compound was measured and found to be 960. In addition, in 100% by mass of this polysilazane, the (A-1) and (A-2) components were 0% by mass, and the (A-3) component was 100% by mass.
[0066] [Example 1] 70 parts of the polysilazane compound A obtained in Synthesis Example A, 30 parts of anisole, 0.2 parts of palladium acetate, and 525 parts of a silica filler toluene dispersion (TOL-ST: manufactured by Nissan Chemical Co., Ltd., particle size 10 to 15 nm, non-volatile content 40 mass%) were mixed to obtain an intermediate liquid a. This intermediate liquid a was dried under reduced pressure with an evaporator to distill off the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70 mass%, to obtain a coating liquid a. This coating liquid a was applied to a silicon wafer with a thickness of 0.65 mm with a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was checked again, and there was no change compared to before the test.
[0067] [Example 2] 70 parts of the polysilazane compound B obtained in Synthesis Example B, 30 parts of anisole, 0.2 parts of palladium acetate, and 525 parts of a silica filler toluene dispersion (TOL-ST: manufactured by Nissan Chemical Co., Ltd., particle size 10 to 15 nm, non-volatile content 40 mass%) were mixed to obtain an intermediate liquid b. This intermediate liquid b was dried under reduced pressure with an evaporator to distill off the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70 mass%, to obtain a coating liquid b. This coating liquid b was applied to a silicon wafer with a thickness of 0.65 mm with a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was checked again, and there was no change compared to before the test.
[0068] [Example 3] 70 parts of the polysilazane compound C obtained in Synthesis Example C, 30 parts of anisole, 0.2 parts of palladium acetate, and 525 parts of a silica filler toluene dispersion (TOL-ST: manufactured by Nissan Chemical Co., Ltd., particle size 10 to 15 nm, non-volatile content 40 mass%) were mixed to obtain an intermediate liquid c. This intermediate liquid c was dried under reduced pressure with an evaporator to remove the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70 mass%, to obtain a coating liquid c. This coating liquid c was applied to a silicon wafer with a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was checked again, and there was no change compared to before the test.
[0069] [Example 4] 70 parts of the polysilazane compound A obtained in Synthesis Example A, 30 parts of anisole, 0.2 parts of palladium acetate, and 70 parts of zinc oxide (Panatetra: manufactured by Panasonic Corporation, particle size 20 to 40 μm) were mixed to obtain intermediate liquid d. This intermediate liquid d was dried under reduced pressure using an evaporator to remove the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corporation) so that the non-volatile content was 80 mass% to obtain coating liquid d. This coating liquid d was applied to a silicon wafer with a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was checked again, and there was no change compared to before the test.
[0070] [Example 5] 70 parts of the polysilazane compound A obtained in Synthesis Example A, 30 parts of anisole, 0.2 parts of palladium acetate, and 88 parts of a silica filler toluene dispersion (TOL-ST: manufactured by Nissan Chemical Co., Ltd., particle size 10 to 15 nm, non-volatile content 40 mass%) were mixed to obtain an intermediate liquid e. This intermediate liquid e was dried under reduced pressure using an evaporator to distill off the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70 mass%, to obtain a coating liquid e. This coating liquid e was applied to a silicon wafer with a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was checked again, and there was no change compared to before the test.
[0071] [Example 6] 70 parts of the polysilazane compound A obtained in Synthesis Example A, 30 parts of anisole, 0.2 parts of palladium acetate, and 875 parts of a silica filler toluene dispersion (TOL-ST: manufactured by Nissan Chemical Co., Ltd., particle size 10 to 15 nm, non-volatile content 40 mass%) were mixed to obtain an intermediate liquid f. This intermediate liquid f was dried under reduced pressure with an evaporator to distill off the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70 mass%, to obtain a coating liquid f. This coating liquid f was applied to a silicon wafer with a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was checked again, and there was no change compared to before the test.
[0072] [Comparative Example 1] 70 parts of the polysilazane compound D obtained in Synthesis Example D, 30 parts of anisole, 0.2 parts of palladium acetate, and 525 parts of a silica filler toluene dispersion (TOL-ST: manufactured by Nissan Chemical Co., Ltd., particle size 10 to 15 nm, non-volatile content 40 mass%) were mixed to obtain an intermediate liquid g. This intermediate liquid g was dried under reduced pressure using an evaporator to distill off the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70 mass%, to obtain a coating liquid g. This coating liquid g was applied to a silicon wafer with a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and when the appearance after the heat resistance test was checked again, cracks were found to have occurred in the coating film.
[0073] [Comparative Example 2] 70 parts of the polysilazane compound E obtained in Synthesis Example E, 30 parts of anisole, 0.2 parts of palladium acetate, and 525 parts of a silica filler toluene dispersion (TOL-ST: manufactured by Nissan Chemical Co., Ltd., particle size 10 to 15 nm, non-volatile content 40 mass%) were mixed to obtain an intermediate liquid h. This intermediate liquid h was dried under reduced pressure using an evaporator to distill off the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70 mass%, to obtain a coating liquid h. This coating liquid h was applied to a silicon wafer with a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and the wafer was heated at 150 ° C for 3 hours to cure, but did not cure. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was checked again, and the coating thickness was found to have significantly decreased.
[0074] [Comparative Example 3] 70 parts of the polysilazane compound A obtained in Synthesis Example A, 30 parts of anisole, 0.2 parts of palladium acetate, and 210 parts of zinc carbonate (manufactured by Kanto Chemical Co., Ltd.) were mixed to obtain an intermediate liquid i. This intermediate liquid i was dried under reduced pressure using an evaporator to remove the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil Corp.) so that the non-volatile content was 70% by mass, to obtain a coating liquid i. This coating liquid i was applied to a silicon wafer having a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and the coating was cured by heating at 150 ° C for 3 hours. When the appearance after curing was confirmed, voids were generated on the front of the coating film. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and the appearance after the heat resistance test was confirmed again, and more voids were generated compared to before the test.
[0075] [Comparative Example 4] 70 parts of the polysilazane compound A obtained in Synthesis Example A, 30 parts of anisole, and 0.2 parts of palladium acetate were mixed to obtain an intermediate liquid j. This intermediate liquid j was dried under reduced pressure using an evaporator to remove the solvent, and then diluted with Exxol DSP145 / 160 (manufactured by Exxon Mobil) so that the non-volatile content was 70 mass% to obtain a coating liquid j. This coating liquid j was applied to a silicon wafer with a thickness of 0.65 mm using a spin coater so that the coating thickness after curing was 20 μm, and was heated at 150 ° C for 3 hours to be cured. When the appearance after curing was checked, no appearance defects were found. Thereafter, a heat resistance test was performed at 400 ° C for 3 hours, and when the appearance after the heat resistance test was checked again, cracks were found to have occurred in the coating film.
[0076] [Heat resistance test] A heat resistance test was conducted on the coating samples prepared in the examples and comparative examples. The test conditions were to raise the temperature from room temperature to 400°C at 10°C / min, hold for 3 hours, and then naturally cool to room temperature. When the temperature returned to room temperature, the appearance was observed. Note that if the difference (QP) / Q between the film thickness P after the heat resistance test and the film thickness Q after coating was 5% or less, it was considered that there was no change.
[0077] The examples and comparative examples are shown in the following Table 1. The melting point and decomposition temperature of the filler are indicated with "(decomposition)" for the decomposition temperature, and only the numerical value for the melting point is shown. [Table 1]
[0078] In Examples 1 to 6 and Comparative Examples 1 and 4, no poor appearance occurred after curing. On the other hand, in Comparative Example 2, the coating film did not cure even after heating at 150°C. This is presumably because the polysilazane compound used does not contain any of the (A-1) and (A-2) components, and therefore is less likely to form three-dimensional bonds compared to the structure specified in the present invention. Also, in Comparative Example 3, voids were generated after curing. This is thought to be because the decomposition temperature of the filler used is low, and it decomposed at the curing treatment temperature and generated bubbles. Furthermore, the effect was more noticeable during the heat resistance test at 400°C.
[0079] In the appearance after the heat resistance test, almost no change was observed in Examples 1 to 6 compared to before the test, whereas changes in appearance occurred in Comparative Examples 1 to 4. It is believed that in Comparative Examples 1 and 2, the (A-1) component and the (A-2) component defined in the present invention were less than 50 mass % of the total polysilazane compound, and therefore sufficient heat resistance was not obtained. In Comparative Example 4, since no filler was added, the curing shrinkage stress of the polysilazane resin was large, and further stress due to the difference in linear expansion coefficient between the substrate and the coating film at high temperature was added, which is believed to have caused cracks.
[0080] From these facts, it can be said that the highly heat-resistant coating material of the present invention is stable even at high temperatures of 400°C and is resistant to cracks and film loss.
[0081] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. A highly heat-resistant coating composition comprising the following component (A) and component (B): (A) A polysilazane compound containing a structure represented by the following general formula (A-1), wherein the structure represented by the general formula (A-1) accounts for 50 to 100% by mass of the entire polysilazane compound: (B) Inorganic filler having a melting point and decomposition temperature of 400° C. or higher 【Chemistry 1】 (In the formula, R 1 is a group selected from an aliphatic hydrocarbon group having 1 to 6 carbon atoms and an aromatic hydrocarbon group having 6 to 12 carbon atoms, and in the polysilazane compound, R 1 may be the same or different.)
2. R in the general formula (A-1) 1 2. The highly heat-resistant coating composition according to claim 1, characterized in that: is a methyl group.
3. 3. The highly heat-resistant coating composition according to claim 1, wherein the component (B) is selected from the group consisting of silica, alumina, zinc oxide and titanium oxide.
4. 4. The highly heat-resistant coating composition according to claim 1, wherein the average particle size of the component (B) is within the range of 5 to 100 nm.
5. 5. The highly heat-resistant coating composition according to claim 1, wherein the component (B) is contained in an amount of 50 to 500 parts by mass per 100 parts by mass of the component (A).
Citation Information
Patent Citations
Forming method for ceramic heat resistant insulative coating film
JP1993081926A
Silicone resin composition and heat-resistant insulated wire
JP1994001847A
Method for synthesizing polysilazane excellent in film strength, and heat-resistant insulated wire coated with the same and baked
JP1994136131A
Polysilazane composition
JP1996325460A
Method for coating ceramic coating film and coated material
JP1999043782A